Climate-Adaptive Water Productivity Building Coherence across Food, Water, & Land - Oct. 31, 2023 - CGIAR Initiative on National Policies and Strategies (CGIAR, 2023)
Video highlights from the CGIAR Research Initiative on National Policies and Strategies (NPS) session at the Cairo Water Week on October 31, 2023, conducted focusing on the empirical analysis of Egypt’s climate-adaptive water productivity programs. This session aims to highlight the multifaceted aspects of water productivity and emphasize the existing and best practices.